STRATEGI KEPALA SEKOLAH DALAM MEMBANGUN KARAKTER DISIPLIN GURU DI SEKOLAH DASAR - Sri Haryanti; Sutama, Sutama; Ahmad Fathoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore how the principal's strategies in building teacher discipline character at SD Negeri 03 Ngepungsari, Jatipuro, Karanganyar. This qualitative descriptive research collected data through observation, interviews, and documentation. The results show that the principal's strategies in building teacher discipline character at SD Negeri 03 Ngepungsari focus on several main aspects: enforcing rules, monitoring teachers' punctuality in teaching, role modeling, giving rewards and punishments, checking completeness of teaching aids, and providing mentoring to teachers. The principal plays a crucial role as a manager, leader, and supervisor to enhance teacher discipline at the school.